Temporal and Spatial Regulation of the Four Transcription Start Sites of hetR from Anabaena sp. Strain PCC 7120 - Rajagopalan, Ramya (American Society for Microbiology (ASM), 2010)
The filamentous cyanobacterium Anabaena sp. strain PCC 7120 forms nitrogen-fixing heterocysts in a periodic pattern in response to combined-nitrogen limitation in the environment. The master regulator of heterocyst differentiation, HetR, is necessary for both pattern formation and commitment of approximately every 10th cell of a filament to differentiation into a heterocyst. In this study, the individual contributions of four transcriptional start points (tsps) in regulation of transcription of hetR were assessed, and the effects of the regulatory genes patS, hetN, and patA on transcription from the tsps were determined. The tsp located at nucleotide −271 relative to the translational start site (−271 tsp) was the most tightly regulated tsp, and fluorescence from a −271 tsp-green fluorescent protein (GFP) reporter fusion was observed initially in groups of two cells and later in single cells arranged in a spatial pattern that mimicked the pattern of heterocysts that emerged. Conversely, the fluorescence from the −184 and −728/−696 tsp-GFP reporter fusions was uniform throughout filaments. Transcription from the −271 tsp was severely downregulated in a strain in which the patA gene, which encodes a positive regulator of differentiation, was deleted, and it was not detectable in strains overexpressing the genes encoding the negative regulators of differentiation, patS and hetN. In strains lacking the −271 tsp of hetR, pattern formation, the timing of commitment to differentiation, and the number of cells that differentiated into heterocysts were affected. Taken together, these results demonstrate the role of regulation of the −271 tsp of hetR in the genetic network that governs heterocyst pattern formation and differentiation.